PENINGKATAN KETERAMPILAN GULING BELAKANG DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS ANIMASI DI SD NEGERI 3 SUNGAPAN KULON PROGO - Sayekti, Khusnul Aswin; Pratyas, Rinda; Pamuji, Juni Teguh (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
The research is aimed at improving the teaching of back rolling by using animation based teaching media in grade four of SD Negeri sungapan 3 Kulon Progo. This research was a classroom action research. It was conducted in three meetings and each meeting showed the stages of the development process of back rolling in the physical education. The subjects of the research were the grade four students of SD Negeri Sungapan 3 in the second semester of the 2011/2012 academic year. The instruments used to collect data were observation sheets, questionnaires, and tests. The data were analiysed descriptively. The reserach result showed that the animation based teaching media in the teaching and learning process of back rolling could improve the students’ spirit, enthusiasm, fun atmosphere, and their marks. Keywords: media, animation, back rolling